Acute effect of isometric exercise on autonomic parameters in obese and overweight sedentary adults - Espinoza-Salinas, A.; Bobadilla-Olivares, M.; Millaqueo, C.; Núñez, M.; Oyarzun-Chicuy, G.; Cano-Montoya, J.; Peiret-Villacura, L.; Pinto-Correa, P.; Arenas-Sánchez, G. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
Introduction: Obesity is understood as a chronic inflammation associated with complications in the autonomic nervous system dysfunction related to cardiovascular diseases. And isometric exercise, represented by manual grip strength, favors the reduction of cardiovascular risk and autonomic imbalance. Objective: to describe the acute response of an isometric exercise (IE) compared to the effect of an aerobic exercise (AE), analyzing the autonomic parameters of heart rate variability (LF/HF), diastolic blood pressure (DBP), systolic blood pressure (SBP) and heart rate (HR) in obese and overweight people. Methodology: 20 participants were randomly distributed into 2 groups; those who performed an aerobic exercise session on a cycle ergometer for 15 min at 50 watts (n=10) and those who performed an IE session at 30% of maximal strength (n=10). Both were evaluated pre and post intervention, the variables were analyzed using the Mann-Whitney U statistical test with a significance level of p<0.05. Results: IE produced statistically significant changes in SBP (p= 0.001), LH/HF (p=0.02) and HR (p=0.018), while DBP improved, but not significantly. Conclusions: an EI session generates a greater decrease than EA in HRV, HR and SBP variables.